Genomic Analyses and New Breeding Technologies for the Enhancement of Horticultural Plants - Chen, Fei; Xue, Jia-Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Since the first release of a horticultural crop (grapevine) genome in 2007, hundreds of genome sequences from horticultural plants have been made available to the public. These sequences have facilitated the decoding of genes responsible for the horticultural traits of horticultural crops, including fruit crops, vegetable crops, ornamental crops, beverage crops, and medicinal crops, to an unprecedented degree. In order to promote the findings in this area, Horticulturae is launching a Special Issue entitled "Genomic Analyses and New Breeding Technologies for the Enhancement of Horticultural Plants". The focus of this Special Issue will be analysing the genes responsible for horticultural traits and investigating the use of breeding technologies for horticultural crops.